Does Management℉s Attention to Different Facets of Entrepreneurial Orientation Create Value for the Firm? A Longitudinal Study of Large Retailer. (1st March 2016) - Gupta, Alka; Chen, Jerry; Gupta, Vishal K.
Abstract : Studies of entrepreneurial orientation tend to merge its three components‐proactiveness, risk-taking, and innovativeness‐into a monolithic construct and analyze its relationship with firm outcomes at one point in time. This has resulted in knowledge voids related to the relative importance of the different components, their specific effect on value created by the firm, and their evolution over time. The present study links each component of entrepreneurial orientation to economic value creation using a longitudinal dataset. Results provide support for hypothesized relationships. Implications and avenues for future research are discussed.